Synthesis, Evaluation, and Molecular Docking Study of 4-Monoacyl Resorcinol Against Tyrosinase Enzyme - Danova, Ade; Maulana, Yusuf Eka; Hermawati, Elvira; Chavasiri, Warinthorn (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2023)
Tyrosinase is a crucial enzyme in melanin production to protect the skin from ultraviolet, leading to skin cancers. This study synthesized eight compounds of acyl resorcinol with long-chain carbon (1-8) and structurally elucidated by 1H and 13C NMR. The in vitro evaluation of eight synthesized compounds against tyrosinase enzyme showed that 4-heptanoyl resorcinol (6) exhibited high inhibitory activity compared with the kojic acid as standard. In addition, the molecular docking study demonstrated that 6 showed lower binding energy (-7.3 kcal/mol) than kojic acid (-6.9 kcal/mol) and possessed interaction with crucial residues in the active site.